Tales of the Narts : Ancient Myths and Legends of the Ossetians - Colarusso, John, 1945- (Princeton University Press, 2016)
"The Nart sagas are to the Caucasus what Greek mythology is to Western civilization. Tales of the Narts presents a wide selection of fascinating tales preserved as a living tradition among the peoples of Ossetia in southern Russia, a region where ethnic identities have been maintained for thousands of years in the face of major cultural upheavals. A mythical tribe of tall, nomad warriors, the Narts were courageous, bold, and good-hearted. But they were also capable of cruelty, envy, and forceful measures to settle disputes. In this wonderfully vivid and accessible compilation of stories, colorful and exciting heroes, heroines, villains, and monsters pursue their destinies though a series of peculiar exploits, often with the intervention of ancient gods. The world of the Narts can be as familiar as it is alien, and the tales contain local themes as well as echoes of influence from diverse lands. The ancestors of the Ossetians once roamed freely from eastern Europe to western China, and their myths exhibit striking parallels with ancient Indian, Norse, and Greek myth. The Nart sagas may also have formed a crucial component of the Arthurian cycle. Tales of the Narts further expands the canon of this precious body of lore and demonstrates the passion and values that shaped the lives of the ancient Ossetians."--